A model for enterprise resource planning in emergency humanitarian logistics - Jose V. Gavidia (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – While the need for information systems is regularly highlighted in the humanitarian logistics literature, a detailed model of what such system would look like is missing. The purpose of this paper is to highlight the need and advantages of enterprise resource planning (ERP) technology in humanitarian emergency logistics. The paper also proposes a model for the configuration, maintenance, operation, and improvement of the system. Design/methodology/approach – This conceptual paper uses existing logistics and information systems literature to build the logical case for an integrated enterprise system for humanitarian emergencies, and to propose conceptual content and process models. Findings – The problem of lack of coordination is reviewed, and a holistic solution is proposed through a structure and model of ERP systems technology to meet the specific requirements of humanitarian emergencies. Research limitations/implications – As in any conceptual paper, a limitation of this paper is the lack of empirical validation of the proposed system. It also might be difficult to obtain the cooperation of multiple organizations. This research focuses on emergency humanitarian logistics, where effectiveness and speed have priority over simplicity or cost. Practical implications – The model proposed in this paper links current efforts in humanitarian emergency coordination with existing supply chain information technologies, and is practically feasible both from the technological and organizational perspectives. Social implications – Because of the critical, life or death nature of the problem, social and ethical implications of this research are broad, including the divergence of coordination in humanitarian vs commercial and military logistics, as well as inter-agency politics. Originality/value – This paper is a bold but realistic attempt to take a holistic view of humanitarian logistics and design a system that would be effective, and calls humanitarian organizations worldwide to collaborate in its implementation.